ENTERPRISE RISK MANAGEMENT (ERM) SOAR (STRATEGIC OBJECTIVE AT RISK) METHODOLOGY - Fredella Colline (Bina Ekonomi, 2010)
Risk is part of every business decisions.  Risk Management helps enterprises whether to take or avoid some risks that related to their objectives. Risks are by their very nature dynamics, fluid and highly interdependent so that they cannot be broken into separate components and managed independently. Enterprises operating in today's volatile environment require a much more integrated approach to managing their portfolio of risks that is Enterprise Risk Management (ERM) SOAR. Methodology can be used to implement an effective ERM framework. This paper focuses on the application of the SOAR process to risks associated with strategic objectives.  The further explanation will contain the elaboration of SOAR concepts, process and example.Key words: ERM, SOAR, strategic objective, risk drivers, controls, metrics